Implementing Sustainable Development Goals To Achieve Community Welfare: Optimising Presidential Decree 111/2022 - Ginting, Yuni Priskila; Indradewi, Astrid Athina; Kartiko, Nafis Dwi; Hanunisa, Salma Zhafira (LEGAL BRIEF, 2023)
By Presidential Decree 59/2015, sustainable development targets with a global perspective were adopted in Indonesia. The Sustainable Development Goals (SDGs) have been implemented in Indonesia for the past 8 (eight) years, fulfilling a worldwide commitment. It is hoped that by enacting PRESIDENTIAL DECREE 111/2022 concerning the Implementation of Achieving the Sustainable Development Goals, the 2024 national Sustainable Development Goals (SDGs), as outlined in the book Transforming Our World: The 2030 Agenda for Sustainable Development, can be accomplished more quickly and with a more focused approach. A statutory approach and a normative juridical research methodology were adopted. The 2030 Plan for Sustainable Development is comprised of the Sustainable Development Goals. The advancement towards reaching the Sustainable Development Goals (SDGs) over the past 10 (ten) years has been undermined by a string of extraordinary global crises. To advance human development, technological mastery, a sustainable economy, equitable development, and strengthening of national resilience and governance, development pillars are required